Statistics and Skepticism of Influencer Marketing: Efficiency and Future Growth Perspectives - Peng, Chelsea (Current Topics on Business, Economics and Finance Vol. 7, 2023)
This chapter examines the exponential growth of the influencer industry in recent years, as well as the challenges associated with measuring the efficacy of influencer marketing and advertising in general. Influencer Marketing Hub defines influencers as people with the power to affect buying habits of consumers through social media, and influencer marketing as a brand working with one of these influencers either to market their products or services or simply just to improve brand reputation. Using data related to negative consumer impressions of traditional advertising features like pop-up ads and the untrustworthy review phenomenon and relating it to data about Generation Z’s modern opinions on social media marketing, this study explains how influencer marketing is the better choice to appeal to a younger audience. Three characteristics—physical beauty, social attractiveness, and attitude homophily—are reinforced in the development of pseudo-social interactions between the influencer and the customer. The main difference between influencer marketing and traditional marketing is the emotional and personal connection that the marketer, the influencer, can form with social media users.